INDONESIAN LANGUAGE LEARNING TRAINING FOR FOREIGN SPEAKERS: INTRODUCE INDONESIAN FOR FOREIGN SPEAKERS TO LANGUAGE CLASS STUDENTS - Refa Lina Tiawati; Suci Dwinitia; Yulia Pebriani (Universitas PGRI Sumatera Barat, 2021)
This training is aimed at class XII language students at the State University of Padang State University Laboratory Development High School. The method used is the lecture and discussion method. The material presented aims to introduce students that BIPA is teaching Indonesian as a foreign language and not a second language. Indonesian is taught so that foreigners can live and suevive in Indonesian nature and culture. One of the frameworks is the CEFR (Common European Frame of Reference) for language. In BIPA learning, there are several things that must be considered between BIPA learning strategies and media. The discussion method is also used for questions and answers with students related to their understanding of the material that has been delivered.